Fate Or Fixable? Exploring Teachers Beleifs About Treatable Birth Defects - Ahmad, Salman; Daud, Anum; Khan, Uzma; Fazil, Saman; Khan, Awais; Ahmad, Sheraz; Khan, Zeeshan; Tashfain Ali, Safarat; Mukhtar, Shuraim; Khayam, Muhammad (Journal of Neonatal Surgery, 2025)
BACKGROUND: One of the main causes of avoidable newborn morbidity and mortality worldwide is congenital abnormalities. In many communities, awareness is still poor despite the availability of effective preventive strategies like folic acid use and prenatal screening. Although school teachers are vital sources of health information, little is known about their knowledge, attitudes, and practices (KAP) surrounding baby abnormalities. This study assesses and compares the KAP of urban and rural school teachers in Peshawar, Pakistan. METHODS: For a cross-sectional study, 384 elementary and secondary school teachers from Peshawar's urban and rural districts were selected using multistage random sampling. A standardized questionnaire was used to assess knowledge (7 questions), attitudes (5 items), and behaviors (5 things). Using SPSS version 26, the data was examined using chi-square tests and descriptive statistics; p < 0.05 was considered significant. RESULT: Among the participants, 30.2% had low knowledge and 45.1% had strong knowledge. The knowledge levels of urban teachers were significantly greater than those of rural teachers (55.4% vs. 34.7%, p < 0.001). Positive assessments were higher for teachers in rural areas (49.2% vs. 44.6%, p = 0.030). Practices were generally insufficient, with only 1.8% attaining adequate practice and 70.1% exhibiting inadequate practice. The practice scores of teachers in rural areas were significantly lower than those in urban areas (74.9% vs. 65.3%, p = 0.040). CONCLUSION : There is a terrible lack of awareness, attitudes, and preventative measures among teachers regarding abnormalities in neonates. Teachers in both urban and rural areas exhibited negative behaviors despite their generally upbeat moods and low competence levels. To assist community-level prevention, it is crucial to improve teacher preparation, incorporate neonatal health awareness into school curricula, and strengthen cooperation with health authorities.